Analog circuit design a tutorial guide to applications and solutions - Dobkin, Bob; Williams, Jim 1948-2011 (Newnes, 2011)
* Covers the fundamentals of linear/analog circuit and system design to guide engineers with their design challenges. * Based on the Application Notes of Linear Technology, the foremost designer of high performance analog products, readers will gain practical insights into design techniques and practice. * Broad range of topics, including power management tutorials, switching regulator design, linear regulator design, data conversion, signal conditioning, and high frequency/RF design. * Contributors include the leading lights in analog design, Robert Dobkin, Jim Williams and Carl Nelso.
Includes bibliographical references and index. - Print version record
Keywords: Electronic circuit design; Electronic analog computers -- Circuits; Linear integrated circuits -- Design and construction; Electric filters -- Design and construction; Low voltage integrated circuits -- Design and construction; Amplifiers, Radio frequency -- Design and construction; Mixed signal circuits; Circuits électroniques; Calcul; Circuits analogiques; Circuits à signaux mixtes; Amplifiers, Radio frequency; Design and construction; Electric filters; Design and construction; Electronic analog computers; Circuits; Linear integrated circuits; Design and construction; Low voltage integrated circuits; Design and construction